A quantitative study on SCCT: examining the relationships between crisis response strategy, crisis history, and crisis type on organisational reputation: Nigerian perspective - Dominic, Egede Dominion; Mahamed, Mastura; Abdullah, Zulhamri; Hashim, Norliana (Human Resource Management Academic Research Society, 2022)
Organizations are sustained by the strength of their reputations globally and especially in crisis management when the reputations of such organizations are threatened. Thus, effective crisis communications management is indispensable to every organization maintaining its reputation. This research paper used Coombs' Situational Crisis Communication Theory (SCCT) to examine the relationships between crisis response strategy, crisis history, and crisis type on organizational reputation from the lens of the Nigerian perspective. This project was guided by the Situational Crisis Communication Theory (SCCT) since previous research has demonstrated that the variables of the theory might influence organizational reputations. Consequently, the study examined the levels of Nigerian MTN reputation among the 254 respondents. It further evaluated the relationships between crisis response strategy, crisis history, crisis type, and reputation during crisis management. A quantitative research approach was utilized to offer inferential and descriptive findings. The study showed that more than half of the respondents’ reputations for Nigerian MTN were high. The findings further demonstrated positive and significant relationships between crisis response strategy, crisis history, crisis type, and reputation where the p<.01. However, the strength of their relationships with reputation differed. Thus, crisis history contributed most to reputation with t=3.99, follow by crisis type with t=2.80 and crisis response strategy with t=1.57. Therefore, the findings of the study recommend that Nigerian MTN organizations should embrace these factors towards enhancing their reputation during crises. The study further contributed the knowledge on how to universally sustain organizational reputations during crises.